Institutional Strengthening of Farmer Groups through Resource Efficiency and Organizational Management in Konda District, South Konawe Regency - Munadi, La Ode Muh. (Majalah Pengabdian Indonesia, 2025)
This community service aims to improve the efficiency of resource management and organizational management within the Lembah Subur Morome Farmers Group in Konda District, Konawe Selatan Regency. The main issue faced by this farmers group is the lack of efficient resource management and poorly structured organization, which affects productivity and the welfare of its members. Using a participatory approach, training was provided to the group members on organizational management, resource management, and more effective marketing techniques. The results of the service showed improvements in managerial capacity, efficiency in managing natural and human resources, and the ability to market agricultural products. The farmer’s group is now more organized, with more transparent budget management and clearer task division. Additionally, marketing skills through social media have enabled the farmers to expand their market reach and increase income. This service is expected to contribute positively to agricultural development and the improvement of farmers' welfare in Konda District.